Neurofibromatoses in clinical practice - Ferner, Rosalie E.; Huson, S. M.; Evans, D. Gareth R. (London, England Springer, 2011)
Neurofibromatoses in clinical practice provides a succinct, accessible guide to the neurofibromatoses including diagnosis, management protocols and indications for referral to specialist centers. Neurocutaneous diseases are complex to diagnose and treat and many patients require specialist multidisciplinary management and surveillance. Due to multiple disease manifestations, patients can present to different clinicians without specialist expertise such as general practitioners, pediatricians, neurologists, geneticists, surgeons and ophthalmologists. The clinically focused format of this book will enable rapid consultation during clinics, facilitate disease pattern recognition, and indicate care pathways. The clinical quiz highlights common pitfalls in diagnosis and management and a glossary and reference section provide details for access to specialist NF clinics throughout the UK and internationally. Written by experts in the field Neurofibromatoses in Clinical Practice is a practical guide for consultants in training and practice, general practitioners and specialist nurses.
Introduction--Neurofibromatosis 1--Neurofibromatosis 2--Differential diagnosis of NF1 and NF2 -- Psychological impact of disease and quality of life -- Clinical quiz emphasising diagnostic and management pitfalls of neuruocutaneous disease--Glossary of terms--Useful websites for NF information, lay groups and specialist NF centres.
Electronic reproduction.
Keywords: Neurofibromatosis